Challenges And Opportunities in The Internationalization of Islamic Higher Education - Supriatna, Dasep; Windarta, Libri Rizka Puri; Syamsuri, Syamsuri (Fenomena, 2025)
The internationalization of Islamic Higher Education Institutions (IHEIs) remains understudied despite its growing significance in global higher education. While mainstream institutions have been extensively researched, IHEIs face unique challenges due to their religious identity, mission, and distinct stakeholder expectations. This study addresses this gap by analyzing IHEIs' internationalization efforts through Resource Dependence Theory (RDT), which posits that organizations strategize to secure critical external resources. This research utilizes a qualitative multiple-case study design to examine four diverse IHEIs through semi-structured interviews and document analysis. The findings reveal that IHEIs pursue internationalization to access funding, students, faculty expertise, and legitimacy while managing dependencies specific to their. Key strategies include diversifying partnerships, negotiation with accreditors, and adaptation to global standards. Challenges include financial constraints, geopolitical instability, and tensions between Islamic values and secular academic norms. Conversely, opportunities arise from niche student markets, Islamic funding networks, and global collaborations. The study concludes that IHEIs proactively manage dependencies to enhance autonomy and sustainability. By applying RDT, this research provides insights into how IHEIs navigate global higher education dynamics while preserving their religious mission, offering valuable implications for policymakers and institutional leaders. Internasionalisasi Perguruan Tinggi Islam (PTKI) masih kurang diteliti meskipun perannya semakin penting dalam pendidikan tinggi global. Berbeda dengan institusi arus utama yang telah banyak dikaji, PTKI menghadapi tantangan khas yang berkaitan dengan identitas keagamaan, misi, dan ekspektasi pemangku kepentingan yang berbeda. Studi ini mengisi kekosongan tersebut dengan menganalisis upaya internasionalisasi PTKI menggunakan Resource Dependence Theory (RDT), yang menyatakan bahwa organisasi menyusun strategi untuk memperoleh sumber daya eksternal penting. Penelitian ini menggunakan desain studi kasus ganda kualitatif, mencakup empat PTKI yang beragam melalui wawancara semi-terstruktur dan analisis dokumen. Hasilnya menunjukkan bahwa PTKI mengejar internasionalisasi guna memperoleh pendanaan, mahasiswa, keahlian dosen, dan legitimasi, sambil menyeimbangkan ketergantungan yang terkait dengan identitas Islam. Strategi utama meliputi diversifikasi kemitraan, negosiasi dengan lembaga akreditasi, dan adaptasi terhadap standar global. Tantangan yang dihadapi meliputi keterbatasan finansial, ketidakstabilan geopolitik, serta ketegangan antara nilai Islam dan norma akademik sekuler. Namun, peluang juga muncul melalui pasar mahasiswa khusus, jaringan pendanaan Islam, dan kolaborasi global. Studi ini menyimpulkan bahwa PTKI secara aktif mengelola ketergantungan untuk meningkatkan otonomi dan keberlanjutan kelembagaan.